Routine versus Targeted Viral Load Strategy among Patients Starting Antiretroviral in Hanoi, Vietnam. Issue 3 (21st March 2019) - Pollack, Todd M; Duong, Hao T; Pham, Thuy T; Nguyen, Thang D; Libman, Howard; Ngo, Long; McMahon, James H; Elliott, Julian H; Do, Cuong D; Colby, Donn J
Abstract: Introduction: HIV viral load (VL) testing is recommended by the WHO as the preferred method for monitoring patients on antiretroviral therapy (ART). However, evidence that routine VL (RVL) monitoring improves clinical outcomes is lacking. Methods: We conducted a prospective, randomized controlled trial of RVL monitoring every six months versus a targeted VL (TVL) strategy (routine CD4 plus VL testing if clinical or immunological failure) in patients starting ART between April 2011 and April 2014 at Bach Mai Hospital in Hanoi. Six hundred and forty‐seven subjects were randomized to RVL (n = 305) or TVL monitoring (n = 342) and followed up for three years. Primary endpoints were death or WHO clinical Stage 4 events between six and thirty‐six months of ART and rate of virological suppression at three years. Results: Overall, 37.1% of subjects were female, median age was 33.4 years (IQR: 29.5 to 38.6), and 47% had a CD4 count ≤100 cells/mm 3 at time of ART initiation. Approximately 44% of study events (death, LTFU, withdrawal, or Stage 4 event) and 68% of deaths occurred within the first six months of ART. Among patients on ART at six months, death or Stage 4 event occurred in 3.6% of RVL and 3.9% of TVL ( p  = 0.823). Survival analysis showed no significant difference between the groups ( p  = 0.825). Viral suppression at 36 months of ART was 97.2% in RVL and 98.9% in TVL ( p  = 0.206) at a threshold of 400 copies/mL and was 98.0% in RVL and 98.9% in TVL ( p  = 0.488) at 1000 copies/mL. In ITT analysis, 20.7% in RVL and 21.9% in TVL ( p  = 0.693) were unsuppressed at 1000 copies/mL. Conclusions: We found no significant difference in rates of death or Stage 4 events and virological failure in patients with RVL monitoring compared to those monitored with a TVL strategy after three years of follow‐up. Viral suppression rates were high overall and there were few study events among patients alive and on ART after six months, limiting the study's power to detect a difference among study arms. Nonetheless, these data suggest that the choice of VL monitoring strategy may have less impact on patient outcomes compared to efforts to reduce early mortality and improve ART retention.